Study the Effect of Perturbation in the Evolution of the Filamentary Molecular Clouds - Maryam Mesgaran; Khodadad Kokabi (Iranian Journal of Astronomy and Astrophysics)
Observatory studies indicate that stars are caused by the collapse of dense molecular clouds, and thermal instability can be a factor in creating this collapse. As the formation of stars occurs in molecular clouds, the evolution of molecular clouds is important. In this study, the stability of the magnetized filamentary molecular clouds and their instability growth rate has been investigated. We consider the linear thermal instability of magnetized filament. We showed that the magnetic field makes the filament more stable against thermal instability. Also, increasing the intensity of the magnetic field helps to reduce the growth rate of instability.